Molecular Diagnosis of Antibody‐Mediated Rejection in Human Kidney Transplants. Issue 4 (15th February 2013) - Sellarés, J.; Reeve, J.; Loupy, A.; Mengel, M.; Sis, B.; Skene, A.; de Freitas, D. G.; Kreepala, C.; Hidalgo, L. G.; Famulski, K. S.; Halloran, P. F.
<x xml:space="preserve">Abstract</x> Antibody‐mediated rejection is the major cause of kidney transplant failure, but the histology‐based diagnostic system misses most cases due to its requirement for C4d positivity. We hypothesized that gene expression data could be used to test biopsies for the presence of antibody‐mediated rejection. To develop a molecular test, we prospectively assigned diagnoses, including C4d‐negative antibody‐mediated rejection, to 403 indication biopsies from 315 patients, based on histology (microcirculation lesions) and donor‐specific HLA antibody. We then used microarray data to develop classifiers that assigned antibody‐mediated rejection scores to each biopsy. The transcripts distinguishing antibody‐mediated rejection from other conditions were mostly expressed in endothelial cells or NK cells, or were IFNG‐inducible. The scores correlated with the presence of microcirculation lesions and donor‐specific antibody. Of 45 biopsies with scores >0.5, 39 had been diagnosed as antibody‐mediated rejection on the basis of histology and donor‐specific antibody. High scores were also associated with unanimity among pathologists that antibody‐mediated rejection was present. The molecular score also strongly predicted future graft loss in Cox regression analysis. We conclude that microarray assessment of gene expression can assign a probability of ABMR to transplant biopsies without knowledge of HLA antibody status, histology, or C4d staining, and predicts future failure.